Multi-Parametric Study of the Viability of in Vitro Skin Cancer Cells Exposed to Nanosecond Pulsed Electric Fields Combined With Multi-Walled Carbon Nanotubes. (24th September 2019) - Mi, Yan; Li, Pan; Liu, Quan; Xu, Jin; Yang, Qiyu; Tang, Junying
Multi-walled carbon nanotubes with excellent electrical properties and high aspect ratios can reduce the high field strength required to kill cancer cells in vitro with nanosecond pulsed electric fields. For the first time, this article systematically and comprehensively evaluates the effects of various parameters of nanosecond pulsed electric fields combined with multi-walled carbon nanotubes on cell viability. The effects of field strength, E (2-10 kV/cm); pulse width, τ (100-500 ns); and pulse number, N (5-260) on the viability of A375 human skin cancer cells in the presence of multi-walled carbon nanotubes are studied using the Cell Counting Kit 8 assay. Based on a logistic model, the relationship between cell viability and various parameters is obtained using 1-dimensional nonlinear fitting. The results show a sigmoid-type variation in cell viability with field strength, pulse width, or pulse number. Multivariate scaling analysis shows that the relationship between cell viability and the pulse energy density σE 2 τN can be described as a sigmoid type. The introduction of multi-walled carbon nanotubes does not affect the above rules but significantly enhances the killing effect of nanosecond pulsed electric fields, which could effectively improve the electrical safety of nanosecond pulsed electric fields for the treatment of tumors.